Ex vivo biomechanical investigations of combined extra- and intracapsular stabilization in canines with cranial cruciate ligament deficiency - Sun, Cheng-Yuan; Lin, Cheng-Chung; Wu, Ching-Ho (Frontiers in Veterinary Science, 2024)
Intracapsular reconstruction (ICR) has long been recommended as a treatment for cranial cruciate ligament deficiency (CCLD) in dogs, but it has fallen out of favor due to its inferior long-term functional outcomes. These outcomes may be attributed to the poor stiffness and strength of the graft in the early period before ligamentization is completed. Additional placement of extracapsular sutures to mechanically protect the graft during the ligamentization process may be a viable method to address this problem. However, the biomechanical effect of this combined surgical approach remains unknown. This study aimed to evaluate the 3D kinematics of the CCLD stifle in dogs in response to ICR and combined extra- and intracapsular reconstruction (CEICR). Twelve hindlimbs were collected from nine cadavers of mature dogs. The limbs were tested using a custom-made testing apparatus that reproduces their sagittal plane kinematics during the stance phase. Four statuses of stifle joints were tested, namely, (a) cranial cruciate ligament (CCL) intact; (b) CCLD; (c) CCLD stifle stabilized by CEICR; and (d) CCLD stifle stabilized by ICR only. Three-dimensional stifle kinematics at the 5 instances of the stance phase were measured with an optoelectronic system. The results showed that ICR marginally corrects the increased adduction, internal rotation, and caudodistal stifle joint center displacement that occur as a result of CCLD. CEICR led to better restoration of the stifle kinematics, especially with respect to the internal rotation and cranial translation stabilities. Furthermore, CEICR only resulted in minor excessive restraints on other motion components. The findings indicated that the additional lateral fabellotibial suture offers immediate stability to the stifle, consequently lowering the risk of graft over-elongation in the short term postoperatively. Considering the propensity for the extracapsular suture to degrade over time, further in vivo studies are warranted to explore the long-term effects of the CEICR procedure.